IMPROVING LEARNING ACHIEVEMENT THROUGH INTERPERSONAL INTELLIGENCE AND SELF-REGULATED LEARNING - Retno Purwitasari; Mardi Mardi; Ayatulloh Michael Musyaffi (Yayasan Education and Social Center, 2023)
The material in accounting computer lessons utilizes technology to present problems to students. Thus, generating differences in student achievement based on various factors and investigating the relationship between student success and factors such as interpersonal intelligence and self-regulated learning. This study uses a survey method based on a quantitative approach. The Affordable population of this study is the eleventh-grade students in the Department of financial accounting SMKN Jakarta with 174 students. Simple random sampling is used as a sampling technique. The sample was taken randomly without certain criteria so that students with high or low achievement could be a research sample. Known results of this study's average (mean) student achievement into Category B (Good). Furthermore, students with interpersonal intelligence and self-regulated learning are in the